Penangkapan Lobster Air Tawar di Danau Laut Tawar Kabupaten Aceh Tengah dengan Alat Tangkap Bubu Wau - Muklis, Muklis Muklis; Artelin, Nisma; Aprilla, Ratna Mutia (Jurnal TILAPIA, 2025)
Laut Tawar Lake is located in Takengon City, Central Aceh Regency. Currently, the lake is utilized by the surrounding community as a lobster fishing area. The fishing gear used by the fishermen includes bubu wau traps and other fishing tools. The main catch from the bubu wau traps used by the fishermen in One-One Village is freshwater lobster, a species found in Laut Tawar Lake. The freshwater lobsters caught in One-One Village have a high market value, which is why most fishermen in the area use bubu wau traps. These traps allow better control over the size of the lobsters caught, depending on the trap’s mesh size. The shift from catching depik fish to freshwater lobsters has increased interest in the use of bubu wau traps. One of the current research focuses is freshwater lobster fishing using bubu wau traps; thus, we believe this study is necessary. Based on the findings during the study, the species caught was Cherax quadricarinatus, with the most frequently caught size being those with a carapace length of 4.4–4.9 cm, and the least frequently caught size being 8.6–9.1 cm.